Teaching Global Warming with Millealab Virtual Reality - Agusty, Alifia Ilwi; Anggaryani, Mita (Jurnal Pendidikan Fisika, 2021)
Virtual Reality (VR) is a new technology in education applied to the learning process. The development of VR technology in education meets several problems. This research develop a learning media based on virtual reality technology developed by Millealab. Millealab is a platform for developing VR media with more specific features to create a good visualization of reality to support the teaching and learning process. The development of VR media named "GoWarm with Millealab" has been made through researching, creating, validating, and trial. The validation process was assessed by six validators (Physics media lecturers, Physics teachers, and media experts) and got an average score of 87%. It means the media is good and very valid. The trial was limited and conducted online because of the COVID-19 pandemic. The result shows that the media is categorized as very good. Indeed, "GoWarm with Millealab" received positive feedback from the respondents (20 high school students). In brief, "GoWarm with Millealab" is successfully developed to gain attention to Global Warming issues. Further research in VR-based physics learning media needs to be done by improving content and evaluation.